2012
DOI: 10.3141/2278-11
|View full text |Cite
|
Sign up to set email alerts
|

Response Time of Highway Traffic Accidents in Abu Dhabi

Abstract: Traffic incidents generate many adverse impacts, especially as far as traffic congestion, air pollution, fuel consumption, and secondary crashes are concerned. Therefore traffic incident responders and operators must know how to improve the efficiency of traffic incident management. This paper presents the results of an investigation into the effects of traffic accident characteristics on accident response time, with fully parametric hazard-based duration models with emphasis on the accelerated failure time me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 15 publications
(18 reference statements)
1
5
0
Order By: Relevance
“…Few studies include incident detection and recovery time [23], as well as define the duration time as the time difference from the time the Freeway Courtesy Patrol (FCP) vehicle arrives on the scene to the time the FCP leaves the scene after clearing the incident [24]. Other studies focus on the clearance time [11,[24][25][26][27], response time [28,29], or different time phases [9,30]. One study divides the response time into two parts: preparation time of the response team and travel time of the response vehicles [29].…”
Section: Different Traffic Incident Time Phasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies include incident detection and recovery time [23], as well as define the duration time as the time difference from the time the Freeway Courtesy Patrol (FCP) vehicle arrives on the scene to the time the FCP leaves the scene after clearing the incident [24]. Other studies focus on the clearance time [11,[24][25][26][27], response time [28,29], or different time phases [9,30]. One study divides the response time into two parts: preparation time of the response team and travel time of the response vehicles [29].…”
Section: Different Traffic Incident Time Phasesmentioning
confidence: 99%
“…Several studies reveal that the traffic duration time meets the log-normal distribution [12,13,21] or log-logistic distribution [9,31,36,39,41,42]. Weibull distribution (or with gamma heterogeneity or random parameters) provides the best likelihood ratio statistics for the used dataset in some other studies [9,23,25,28,37]. Several other studies report that the generalized F distribution is the best type for the traffic duration time distribution [24,26].…”
Section: Duration Time Distributionmentioning
confidence: 99%
“…Sanchez et al [11] observed that a 10 min reduction in the response time can reduce the likelihood of death by one-third. Assessment of response time has been found effective in identifying the gaps and scopes for improvement in the accident management systems in Abu Dhabi [12]. However, such evidence is lacking in the KSA.…”
Section: Introductionmentioning
confidence: 99%
“…Cornelia [10] also indicated that the rate of dying in a traffic accident in a tunnel is almost twice that elsewhere, and regardless of whether the traffic flow is two-way or one-way, the probability of a traffic accident at the tunnel entrance is higher than that elsewhere in the tunnel. As a bottleneck in an expressway, when an accident happens in a tunnel, it can easily lead to secondary accidents [11]. Therefore, it is very important to make tunnel traffic safer.…”
Section: Introductionmentioning
confidence: 99%